2022
DOI: 10.3390/ijerph19169935
|View full text |Cite
|
Sign up to set email alerts
|

Historical Changes in Weight Classes and the Influence of NAFLD Prevalence: A Population Analysis of 34,486 Individuals

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease globally in tandem with the growing obesity epidemic. However, there is a lack of data on the relationship between historical weight changes 10 years ago and at present on NAFLD prevalence at the population level. Therefore, we sought to evaluate the relationship between weight classes and the prevalence of NAFLD. Methods: Data were used from the United States National Health and Nutrition Examination Survey (NHANES)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…The Coronary Artery Risk Development in Young Adults study reported that participants with an increase in BMI had greater odds of NAFLD compared to those with stable BMI using the trajectory modeling [22]. Nah et al [23] found significant association between historical weight changes 10 years ago and the present NAFLD prevalence. They showed that participants who progressed to obesity or overweight had higher risk for NAFLD [23].…”
Section: Discussionmentioning
confidence: 99%
“…The Coronary Artery Risk Development in Young Adults study reported that participants with an increase in BMI had greater odds of NAFLD compared to those with stable BMI using the trajectory modeling [22]. Nah et al [23] found significant association between historical weight changes 10 years ago and the present NAFLD prevalence. They showed that participants who progressed to obesity or overweight had higher risk for NAFLD [23].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the marginal effect of ectopic fat distributions on the predictive probability of having NAFLD were more significant in non-obese NAFLD relative to obese NAFLD. The importance of weight remains key in the management principle for NAFLD [ 31 , 32 ]. However, there should also be a wholesome reduction in fat mass beyond visceral fats which are most commonly associated with NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD in the presence of a normal BMI may also be more common among Asian- and African Americans [32]. Normal-weight individuals were more likely to develop NAFLD if they had overweight [relative risk (RR): 2.24, 95% confidence interval (CI) 1.42–3.54] or obesity (RR: 2.46, 95% CI: 1.40–4.31) 10 years prior, implying a residual long-term effect of previous adiposity [33 ▪ ].…”
Section: Clinical Characteristics Of Nonalcoholic Fatty Liver Disease...mentioning
confidence: 99%